Experimental evidence for long‐term coexistence of copiotrophic and oligotrophic bacteria in pelagic surface seawater. (21st November 2020) - Li, Yi; Wang, Zhi‐Bin; Zhang, Xi‐Ying; Dang, Yan‐Ru; Sun, Lin‐Lin; Zhang, Wei‐Peng; Fu, Hui‐Hui; Yang, Gui‐Peng; Wang, Min; McMinn, Andrew; Chen, Xiu‐Lan; Chen, Yin; et al.
Summary: Most marine copiotrophic bacteria can produce extracellular enzymes to degrade biopolymers into bio‐available smaller solutes, while oligotrophic bacteria usually cannot. Bacterial extracellular enzymes and enzymatic products can be a common resource that could be utilized by both copiotrophs and oligotrophs; when present, oligotrophs may outcompete the enzyme‐producing copiotrophs. However, copiotrophs and oligotrophs consistently coexist in the ocean. How they maintain coexistence has still not been experimentally studied. In this study, the interaction and coexistence of a copiotroph and an oligotroph, isolated from the same surface seawater sample and utilizing the same proteinaceous substrate, were experimentally investigated. The copiotroph could secrete extracellular proteases to degrade and then utilize the proteinaceous substrate. The oligotroph was unable to utilize the proteinaceous substrate by itself, but could grow by using the hydrolysate amino acids. The copiotroph outcompeted the oligotroph by adsorbing the amino acids quickly and having a higher growth rate in the rich medium. The oligotroph survived by adapting to low concentration of nutrients. The copiotroph and oligotroph were able to maintain long‐term (up to 142 days) coexistence in the laboratory. This study indicates that differences in the utilization of different concentrations of nutrients can drive the coexistence of marine copiotrophs and oligotrophs.